Effect of energy drinks on the human body - Nishonov, Utkirali; Atakhanov, Shuxratjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the article, effective work carried out by our state in order to provide the population with food products, public safety, diseases caused by the increase in the amount of caffeine in the products, anti-selling measures and information are mentioned.